Code Ready? Evaluating Basic Life Support Awareness in Nursing Students: Code Ready? Evaluating Basic Life Support Awareness - Keerio, Lal Khan; Memon, Khalida Naz; Soomro, Fatima; Lal, Chhagan; Ali, Roshan; Khatoon, Janual; Dean, Rubina; Ali, Nazish Nawaz (Pakistan BioMedical Journal, 2025)
Basic Life Support (BLS) is a critical skill for nurses, yet gaps remain in both awareness and technical proficiency among nursing students in low and middle-income countries. In Pakistan, limited simulation-based training may impact confidence and competence in cardiopulmonary resuscitation (CPR). Objectives: To assess BLS awareness, self-perceived competence, and associated demographic factors among post-RN BScN students in Sindh, Pakistan. Methods: A descriptive cross-sectional study was conducted between May and November 2022 across five nursing institutes, a structured questionnaire collected data on BLS awareness, CPR technique knowledge, attitudes, and self-perceived competence. A total of 378 students were recruited via convenience sampling. Descriptive statistics were calculated, and chi-square tests were used to examine associations between demographic variables and perceived BLS competence. Results: Most participants (86.2%) had heard of BLS and supported its inclusion in curricula (81%). However, correct responses on technical CPR skills such as the CAB sequence (51.9%), compression depth (56.3%), and 30:2 ratio (43.9%) were suboptimal. Statistically significant associations were found between self-perceived competence and gender, age, clinical experience, and academic year (p<0.05), with males and experienced students rating themselves more highly. Conclusions: The study found high BLS awareness but gaps in technical skills. Integrating simulation-based training, refresher sessions, and addressing gender confidence gaps is essential to improve patient care.